Response of Rice (Oryza sativa L.) Growth and Productivity to the Combination of Cow Manure and Biofertilizer in Lebak Rice Fields - Noviyadi; Neni Marlina; Asvic Helida (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Lowland rice fields are suboptimal land with high acidity constraints and limited nutrient availability, thus requiring an appropriate and sustainable fertilization approach. These conditions make rice a commodity that requires special attention in nutrient management, considering that rice is the main food crop cultivated in lowland swamps but is sensitive to Fe and Al toxicity and nutrient deficiencies in acidic soil conditions. This study aims to examine the growth and productivity response of rice (Oryza sativa L.) to a combination of cow dung manure and biofertilizer in lowland rice fields. The study was conducted in Petar Village, Sungai Rotan District, Muara Enim Regency, South Sumatra Province, using a non-factorial Randomized Block Design (RBD) with five treatments and five replications, namely: no treatment, 100% recommended fertilizer dose, cow dung manure, cow dung manure + ½ recommended fertilizer dose, and biofertilizer + ½ recommended fertilizer dose. The parameters observed included plant height, total number of tillers, productive tillers, panicle length, number of full grains, full grain weight, root length, and productivity (tons/ha). Data were analyzed using ANOVA at the 5% level and continued with Tukey's test. The results showed that the treatment of cow dung manure + ½ dose of recommended fertilizer consistently produced the best values in all growth and productivity parameters, with the highest grain yield of 5.34 tons/ha, significantly different from all other treatments. The treatment of biofertilizer + ½ dose of recommended fertilizer produced a productivity of 4.88 tons/ha and ranked second best. The integration of organic materials and biofertilizers with reduced doses of inorganic fertilizers proved to be more efficient than the use of full doses of inorganic fertilizers alone in increasing rice growth and productivity in lowland rice fields.